Pengaruh Vitamin C terhadap Peningkatan Hemoglobin (Hb) Darah dan Kelulushidupan Benih Ikan Kerapu Bebek (Cromileptes altivelis) - Siregar, Yusni Ikhwan; Adelina, Adelina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
This research was conducted from Maret until June 2008, in Big Hall of Development Marine Aquaculture Lampung.The research used experimental methodology, with 4 treatments and 3 replications. The aimed of research are toknow effects of vitamin C to increase a haemoglobin of blood and survival rate and measured effective C vitaminin prawn of humback grouper. The result showed that the highest haemoglobin rate of at PC (2 g/kg prawn), equalto 0,915 g/100 mL. The lowest haemoglobin found at treatment PA. equal to 0,066 g/100 mL. Result of variansianalysis indicate that addition of vitamin C at food give influence to increase the haemoglobin rate (P<0.05).Survival rate after experiment are 100 %. Parameter of water quality of were: temperature 29.3-30.2 oC, pH 7.81-8.27, salinitas 31-32 psu, DO 3,65-5 mg/L, and ammonia content (NH 3) 0.044-0.069 mg/1